Historical reminiscences: 40 years of the magazine O Mundo da Saúde - Pessini, Leo (O Mundo da Saúde, 2017)
In 2017, in the area of Camillian publications, we have an important fact to be remembered and celebrated: the 40 years of uninterrupted publication of the magazine “O MUNDO DA SAÚDE”. It is a scientific publication linked to the dimension of university education of the Brazilian Camillian Province. It was with great pleasure and joy that I received the honorable invitation of the current editor-in-chief of this publication and President of the São Camilo University Center (SP), Father João Batista Gomes de Lima, to write something concerning the 40-year commemorative edition of this journal. More than a scientific article, which others will certainly do, in their time, I take the liberty of elaborating a historical reminiscence of some of the most striking facts of this trajectory covering four decades. The authenticity and faithfulness of the most striking facts I describe of the trajectory of these 40 years, is due to the fact that I have intensely lived the history of this publication for many years. I was in the direction of the same with the responsibility of being its editor-in-chief (the third in this history of 4 decades) for 20 years, from 1995 to 2014. Moreover, in the late 1970s, more precisely in March 1977, the first issue of this publication appeared, initially quarterly, at which time I was the secretary for three years (1978-1980), while still a student of theology, I graduated at the end of 1980, when I was assigned by the Provincial of that time, to another mission in the Brazilian In this task of recording some “historical reminiscences” of “O Mundo da Saúde”, we will write in three stages. We began with a brief rescue of the emergence of a new publication in the field of health in Brazil, which already envisioned disseminating in its reflections, humanistic, Christian, Camillian values, and presenting to the health community, in general the professionals, a new area of inter, multi and transdisciplinary knowledge, which is bioethics (I). The following is a re-reading of the most striking facts of the scientific and health world that have occurred over the last four decades (1977-2017). We conclude with a look at the future, pointing to the need to face the ethical challenge of always allying science and human and Camillian wisdom, so that we can build a new culture of health care. Camillian Province.